The intriguing complexity of parthenogenesis inheritance in Pilosella rubra (Asteraceae, Lactuceae) - Rosenbaumová, Radka; Krahulcová, Anna; Krahulec, František (Sexual plant reproduction, 2012)
Neither the genetic basis nor the inheritance of apomixis is fully understood in plants. The present study is focused on the inheritance of parthenogenesis, one of the basic elements of apomixis, in Pilosella (Asteraceae). A complex pattern of inheritance was recorded in the segregating F(1) progeny recovered from reciprocal crosses between the facultatively apomictic hexaploid P. rubra and the sexual tetraploid P. officinarum. Although both female and male reduced gametes of P. rubra transmitted parthenogenesis at the same rate in the reciprocal crosses, the resulting segregating F(1) progeny inherited parthenogenesis at different rates. The actual transmission rates of parthenogenesis were significantly correlated with the mode of origin of the respective F(1) progeny class. The inheritance of parthenogenesis was significantly reduced in F(1) n + n hybrid progeny from the cross where parthenogenesis was transmitted by female gametes. In F(1) n + 0 polyhaploid progeny from the same cross, however, the transmission rate of parthenogenesis was high; all fertile polyhaploids were parthenogenetic. It appeared that reduced female gametes transmitting parthenogenesis preferentially developed parthenogenetically and only rarely were fertilized in P. rubra. The fact that the determinant for parthenogenesis acts gametophytically in Pilosella and the precocious embryogenesis in parthenogenesis-transmitting megagametophytes was suggested as the most probable explanations for this observation. Furthermore, we observed the different expression of complete apomixis in the non-segregating F(1) 2n + n hybrids as compared to their apomictic maternal parent P. rubra. We suggest that this difference is a result of unspecified interactions between the parental genomes.
Keywords: Apomixis; apomixie; Reproduction; partenogeneze; typy dědičnosti; rozmnožování; Hybridization, Genetic; Chromosomes, Plant; Inheritance Patterns; Asteraceae; hybridizace genetická; Genome, Plant; Flow Cytometry; průtoková cytometrie; chromozomy rostlin; polyploidie; Polyploidy; genom rostlinný; Parthenogenesis